Modeled Microbial Dynamics Explain the Apparent Temperature Sensitivity of Wetland Methane Emissions. Issue 11 (18th November 2020) - Chadburn, Sarah E.; Aalto, Tuula; Aurela, Mika; Baldocchi, Dennis; Biasi, Christina; Boike, Julia; Burke, Eleanor J.; Comyn‐Platt, Edward; Dolman, A. Johannes; Duran‐Rojas, Carolina; Fan, Yuanchao; Friborg, Thomas; et al.
Abstract : Methane emissions from natural wetlands tend to increase with temperature and therefore may lead to a positive feedback under future climate change. However, their temperature response includes confounding factors and appears to differ on different time scales. Observed methane emissions depend strongly on temperature on a seasonal basis, but if the annual mean emissions are compared between sites, there is only a small temperature effect. We hypothesize that microbial dynamics are a major driver of the seasonal cycle and that they can explain this apparent discrepancy. We introduce a relatively simple model of methanogenic growth and dormancy into a wetland methane scheme that is used in an Earth system model. We show that this addition is sufficient to reproduce the observed seasonal dynamics of methane emissions in fully saturated wetland sites, at the same time as reproducing the annual mean emissions. We find that a more complex scheme used in recent Earth system models does not add predictive power. The sites used span a range of climatic conditions, with the majority in high latitudes. The difference in apparent temperature sensitivity seasonally versus spatially cannot be recreated by the non‐microbial schemes tested. We therefore conclude that microbial dynamics are a strong candidate to be driving the seasonal cycle of wetland methane emissions. We quantify longer‐term temperature sensitivity using this scheme and show that it gives approximately a 12% increase in emissions per degree of warming globally. This is in addition to any hydrological changes, which could also impact future methane emissions. Plain Language Summary: Wet soils such as bogs, fens, and other wetlands emit methane gas. Methane is a powerful greenhouse gas that adds to climate warming. It is important to understand its net production and also how this might change as the Earth warms. Generally, scientists have found that warmer soils emit more methane. However, there is a discrepancy between comparing warm versus cold sites—where the effect of the temperature difference is relatively small—and comparing warmer and colder seasons of the year, where the effect of temperature is much stronger. Since methane emissions are caused by microbes, we investigated whether their behavior might provide an explanation for this discrepancy. We carefully constructed a computer model to simulate the microbes and found that the model could indeed explain the apparent discrepancy in the seasonal and location effects of temperature that was measured. We found that two global climate models did not recreate these seasonal and location effects of temperature until we included the behavior of the soil microbes. Using our new global microbial model, we estimate that there will be around 12% extra methane emission from global wetlands for each degree of global warming, assuming other factors do not change. Key Points: Current Earth system models generally reproduce the observed spatial pattern of wetland methane emissions but not the seasonal dynamics Modeling microbes reproduces observed methane emissions and resolves the discrepancy between the seasonal versus spatial temperature response The modeled long‐term wetland methane emissions increase by 12% per degree of global warming